EVALUASI DAMPAK IMPLEMENTASI KURIKULUM MERDEKA TERHADAP PRESTASI BELAJAR PESERTA DIDIK SEKOLAH DASAR - Afrilya Herianty; Ida Dwijayanti; Sumarno Sumarno (STKIP Subang, 2024)
This research aims to evaluate the impact of implementing the independent curriculum on student learning achievement in elementary schools. The research sample consisted of 15 teachers and 70 students. The research method used involves descriptive statistical analysis, pretest and posttest comparative statistical tests, and regression analysis. The research results show a significant increase in student learning achievement after implementing the independent curriculum. The t-test revealed a significant difference between the pretest and posttest groups (p<0.05), confirming the positive impact of the new curriculum. The evaluation of the implementation of the independent curriculum revealed that all teachers had a good understanding even though they had obstacles in administration which was the main challenge. Student responses show higher motivation, although some face difficulties in learning tasks. Recommendations for future research include the development of more intensive teacher training strategies and increased administrative support. These findings have important implications for Education policy development and provide a basis for further improvements in the Education curriculum at Primary level